Ottawa treaty: from the bottom to the top in the international agenda. a classical multilateral institution? (2010)
The Ottawa Treaty is a milestone in the history of multilateralism. For the first time, thousands of nongovernmental organizations, the UN and the Red Cross, in a coordinated way, captured the attention of governments from around the world on the need to put an end to the use of the landmines (MAP, minas anti persona, in Spanish), a weapon of war that has caused mutilations, deaths and suffering to millions of people. The goal of this paper is to analyze the process from the beginning showing how the topic arose until becoming a matter of international interest, as well as examining the Ottawa Treaty in the light of precepts proposed by theoreticians such as Ruggie (Anatomy of a multilateral institution) and Keohane (legitimacy). It also aims at determining how much the treaty resembles a classical multilateral institution.